A novel missense variant in ultrarare SLC35A1-CDG alters cellular glycosylation, lipid, and energy metabolism without affecting CDG serum markers - Falkenstein, Kristina; Hoeren, Lukas; Kikul, Frauke; Poschet, Gernot; Lüchtenborg, Christian; Brecht, Ines B.; Falb, Ruth; Gauck, Darja; Haack, Tobias; Hecker, Andreas; Himmelreich, Nastassja; Okun, Jürgen G.; et al. (Human mutation, 2025)
SLC35A1-CDG is a very rare type of congenital disorders of glycosylation (CDG) with only five cases known to date. Here, we review the literature and present new data from a sixth patient carrying the uncharacterized variant c.133A>G; p.Thr45Ala in the SLC35A1 gene. In addition to known clinical symptoms of SLC35A1-CDG, the patient presents with failure to thrive, short stature, café-au-lait spot, and preauricular ear tag. Even though examination of CDG markers transferrin (Tf), alpha-1-antitrypsin (A1AT), and apolipoprotein CIII (ApoCIII) revealed no abnormalities in serum, the patient’s fibroblasts showed significant alterations of protein expression or glycosylation of ICAM1, GP130, and TGN46 as well as differences in staining signals of lectins MAL-I, RCAI, and SNA and deviations in LC-MS analysis of total cellular N-glycans. Transfection of CRISPR/Cas9 generated SLC35A1 HEK293 knockout cells with either wild-type SLC35A1 or the c.133A>G variant restored the cellular CMP-Neu5Ac to wild-type levels, making a direct effect of p.Thr45Ala on the function of the transporter unlikely. Instead, our results imply that the residual transporter activity of 65% is caused by a decreased stability of the mutated SLC35A1 protein. Since O-GlcNAcylation was affected as well, energy and lipid homeostasis were analyzed and found to be significantly altered. Notably, proliferation and glycosylation of the SLC35A1-deficient patient fibroblasts were enhanced by supplementation of the cell culture medium with 10 mM GlcNAc.
Online veröffentlicht: 26. Juni 2025
Gesehen am 03.11.2025